Main Requirements to Become a Favorite Teacher at the Raudlatul Ulum 1 Islamic Boarding School, Gondanglegi Malang - Busthomi, Yazidul (Civiliza Publishing, Indonesia., 2025)
Being a teacher is a truly noble job, which is responsible for making people clever in science and have good morals in living this life. A person who initially did not understand anything in front of a teacher is educated to understand life better and get to know the world. This study aims to explore the main capital to become a favorite teacher at the Raudlatul Ulum 1 Ganjaran Gondanglegi Malang Islamic Boarding School. This study uses the type of Field Research and qualitative as its approach because what will be studied is related to the problem of human attitudes and behavior (psychology) and education. The study results indicate that the main capital to become a favorite teacher at the Raudlatul Ulum 1 Ganjaran Gondanglegin Malang Islamic Boarding School, is as follows: 1. Close to students, 2. Building a pleasant atmosphere, 3. Being a friend in learning, 4. Having a sense of compassion, 5. Being patient in teaching, 6. Not arrogant.